Carnivora from the Miocene of Southern Asia and Africa: Biogeographical implications - (:unkn) unknown (My University, 2012)
Carnivoran mammals constitute one of the major components of terrestrial and aquatic ecosystems. They are taxonomically well-diversified and widely distributed during the Neogene period. They first appear in Africa during the early Miocene, broadly contemporaneously with the formation of the “Gomphotherium land bridge”. Throughout the Miocene, the main African dispersal events involving Carnivora are characterized by the immigration of Eurasian taxa, comprising a substantial component of the Southern Asian diversity. Unlike the extensive Siwalik Hills fossil record, Southeast Asian faunal communities are still poorly known, although recent discoveries enhanced their significant role in the biogeographical evolution of mammals. Here we describe new carnivoran faunas from the Middle Miocene of Thailand and Myanmar, from which few and fragmentary Miocene record was previously known. These new faunas include several species of viverrids, mustelids, amphicyonids, felids, and a possible herpestid, and show specific and/or generic similarities notably with carnivoran assemblages from the Middle and Late Miocene of the Siwalik Hills (Pakistan and India), from the Late Miocene of the Yunnan province (China), and from several Early to Late Miocene localities of Africa. We mainly focus our study on two new occurrences of otters (Lutrinae, Mustelidae) from the late Middle Miocene of Chiang Muan and Mae Moh basins (Northern Thailand), from which otter-bearing levels are magnetostratigraphically dated between 12.4-12.2 Ma and 14.2-13.2 Ma, respectively. We report a new species of the piscivorous genus Vishnuonyx, previously recorded in the Middle and Late Miocene of Kenya and in the Middle Miocene of Pakistan and India, as well as the oldest occurrence of the bunodont genus Sivaonyx, which numerous remains are found in the Mio-Pliocene of Central, Eastern and Southern Africa, and in the Late M
Keywords: African Research